(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: The umbilical cord is a coiled tube that stretches from the baby’s belly button to the placenta, containing two arteries and one vein. It supports optimal development and is crucial for nurses to provide care. Specialized training in neonatal intensive care is better suited for treating complex illnesses like umbilical cord infections. Nurses must also be aware of potential complications and comorbidities and collaborate effectively with other healthcare professionals. Proper cord care is essential for newborns’ health and growth trajectory, with a 3-5% prevalence in developing countries. Objective(s): This study aims to assess nurses’ knowledge about umbilical cord care for Neonates. Methodology: A quantitative approach using a descriptive-analysis design was used in the present study in order to assess nurses’ knowledge about umbilical cord care for Neonates.. The period of the study was from January 13th, 2024 to May 13th, 2024. A questionnaire was completed by 64 nurses staff from Welfare Teaching Hospital and Central Teaching Hospital of Pediatric. The sample consisted of 50 nurses. Results: A study was conducted on 64 nurses staff at Welfare Teaching Hospital and Central Teaching Hospital of Pediatric. The questionnaire included 8 items related to gender, age, education, marital status, years of experience, and updated information about umbilical cord care for neonates. A study of nursing participants found that 70% were female and young, with a diverse educational background. Most had 1-2 years of experience, indicating they were relatively new to the profession. Most had up-to-date knowledge about umbilical cord care, but 32% lacked current information. The study found no significant correlation between knowledge levels and gender or hospital experience, but a positive correlation was noted with age and NICU experience. Marital status also correlated positively. Conclusion: The study shows that there isn’t association, between having updated knowledge about Umbilical Cord Care for Neonates in Neonatal Intensive Care Units and the overall knowledge assessment. This implies that while continuous learning is important it needs to be combined with hands on experience for impact. This supports the idea that practical reinforcement plays a role in retaining and applying knowledge as highlighted in theories. Recommendation: Based on these findings it is suggested that nursing education programs and ongoing professional development initiatives should incorporate training in specialized areas like the NICU to improve nurses knowledge and skills. Moreover creating learning environments tailored to nurses of all ages and life stages could be beneficial. Prioritizing practical evidence based training over qualifications alone may be more effective, in enhancing care.